2005
DOI: 10.1097/01.bsd.0000155033.63557.9c
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Outcome of Ossification of the Posterior Longitudinal Ligament (OPLL) of the Thoracic Spine

Abstract: There were five instances of neurologic deterioration in our thoracic OPLL series, and all of them exhibited beak-type OPLL. In the beak-type OPLL, a subtle alteration in the spinal alignment during posterior decompression procedures may increase spinal cord compression, leading to the deterioration of symptoms. A potential increase in kyphosis following laminectomy should be avoided by fixation with a temporary rod. If intraoperative monitoring suggests spinal cord dysfunction, an anterior decompression proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
74
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 6 publications
0
74
0
Order By: Relevance
“…Beak-type OPLL has higher risk of neurological deterioration after posterior approach surgery than flat-type OPLL. 80 Beak-type and flat-type OPLL are shown in Fig. 5.…”
Section: Surgical Treatment Of Thoracic Opllmentioning
confidence: 99%
“…Beak-type OPLL has higher risk of neurological deterioration after posterior approach surgery than flat-type OPLL. 80 Beak-type and flat-type OPLL are shown in Fig. 5.…”
Section: Surgical Treatment Of Thoracic Opllmentioning
confidence: 99%
“…6 Matsuyama et al 7 reported posterior displacement of the spinal cord after laminectomy and concluded that destruction of the posterior spinal structures, such as occurs during a laminectomy procedure, may increase spinal kyphosis, leading to the spinal cord deterioration, in the beak type of thoracic OPLL. CT myelogram demonstrated a beak-type OPLL at the T7-8 level in the present case.…”
Section: Discussionmentioning
confidence: 99%
“…1 The surgical management of thoracic OPLL consists of a multitude of options: posterior decompressive laminectomy, posterior decompressive laminectomy with fusion, anterior decompression through an anterior or lateral approach, anterior decompression through a posterior approach, posterior decompression with fusion followed by anterior or lateral decompression, and laminoplasty. 1,3,4,6,8,9,12,16,20,21,25,[28][29][30][31]34,36,40 Many studies have highlighted the various approaches, but no protocol, paradigm, or definite standard has been identified. 5,36 The optimal objective of surgery for OPLL of the thoracic spine is to completely decompress the spinal cord.…”
Section: Advantages and Disadvantages With Indications And Limitationmentioning
confidence: 99%
“…A classification based on form and morphology includes a continuous or mixed type with a flat shape ("flattype") and a segmental type with sharp protrusions located behind the disc spaces ("beak-type"). 16 Ossification of the posterior longitudinal ligament can also be described morphologically as linear, beaked, continuous waveform, continuous cylindrical, segmental, continuous, or mixed. 15,24 Patterns of ossification can be divided into 4 major subgroups as follows: 1) focal ossification at the posterior margin of the vertebral body; 2) segmental ossification in which each change does not extend beyond the adjacent intervertebral disc level; 3) continuous ossification over multiple levels; and 4) mixed ossification.…”
Section: Anatomical Considerationsmentioning
confidence: 99%
See 1 more Smart Citation